Pengaruh Dukungan Sosial dan Kepemimpinan Transformasional Terhadap Komitmen Organisasi dengan Mediator Motivasi Kerja - Miftahun Ni’mah Suseno; - Sugiyanto (Faculty of Psychology, Universitas Gadjah Mada, 2010)
The purpose of this research was to investigate the influence of social support and transformational leadership toward the three component model of organizational commitment (affective, continuance, and normative) with work motivation as a mediator. Subjects were 94 employees of a sugar factory in Indonesia with minimum 2 years as tenure. Four questionnaire used to obtain the data were organizational commitment questionnaire, social support questionnaire, transformational leadership questionnaire, and work motivation questionnaire. Data were analyzed using regression analysis and partial correlation. Results were: (1) affective and continuance commitments were significantly influenced by social support and transformational leadership with work motivation as mediator and (2) normative commitment was not significantly influenced by social support and transformational leadership. Keywords: organizational commitment, social support, transformational leadership, work motivation.